3D ultrastructural analysis of α‐granule, dense granule, mitochondria, and canalicular system arrangement in resting human platelets. Issue 1 (25th October 2019) - Pokrovskaya, Irina D.; Yadav, Shilpi; Rao, Amith; McBride, Emma; Kamykowski, Jeffrey A.; Zhang, Guofeng; Aronova, Maria A.; Leapman, Richard D.; Storrie, Brian
Abstract: Background: State‐of‐the‐art 3‐dimensional (3D) electron microscopy approaches provide a new standard for the visualization of human platelet ultrastructure. Application of these approaches to platelets rapidly fixed prior to purification to minimize activation should provide new insights into resting platelet ultrastructure. Objectives: Our goal was to determine the 3D organization of α‐granules, dense granules, mitochondria, and canalicular system in resting human platelets and map their spatial relationships. Methods: We used serial block face–scanning electron microscopy images to render the 3D ultrastructure of α‐granules, dense granules, mitochondria, canalicular system, and plasma membrane for 30 human platelets, 10 each from 3 donors. α‐Granule compositional data were assessed by sequential, serial section cryo‐immunogold electron microscopy and by immunofluorescence (structured illumination microscopy). Results and Conclusions: α‐Granule number correlated linearly with platelet size, while dense granule and mitochondria number had little correlation with platelet size. For all subcellular compartments, individual organelle parameters varied considerably and organelle volume fraction had little correlation with platelet size. Three‐dimensional data from 30 platelets indicated only limited spatial intermixing of the different organelle classes. Interestingly, almost 70% of α‐granules came within ≤35 nm of each other, a distance associated in other cell systems with protein‐mediated contact sites. Size and shape analysis of the 1488 α‐granules analyzed revealed no more variation than that expected for a Gaussian distribution. Protein distribution data indicated that all α‐granules likely contained the same major set of proteins, albeit at varying amounts and varying distribution within the granule matrix.